Arithmetic, geometry, cryptography and coding theory: 13th Conference on Arithmetic, Geometry, Cryptography and Coding Theory, March 14-18, 2011, CIRM, Marseille, France : Geocrypt 2011, June 19-24, 2011, Bastia, France - Aubry, Yves (Contemporary mathematics, 2012)
This volume contains the proceedings of the 13th $AGC^2T$ conference, held March 14-18, 2011, in Marseille, France, together with the proceedings of the 2011 Geocrypt conference, held June 19-24, 2011, in Bastia, France. The original research articles contained in this volume cover various topics ranging from algebraic number theory to Diophantine geometry, curves and abelian varieties over finite fields and applications to codes, boolean functions or cryptography. The international conference $AGC^2T$, which is held every two years in Marseille, France, has been a major event in the area of applied arithmetic geometry for more than 25 years.